2002
DOI: 10.1159/000065645
|View full text |Cite
|
Sign up to set email alerts
|

Annualized Incidence and Spectrum of Illness from an Outbreak Investigation of Bell’s Palsy

Abstract: Background: There are limited clinical and epidemiological data on patients diagnosed with Bell’s palsy. While investigating an apparent clustering of Bell’s palsy, we sought to characterize the spectrum of illness in patients with this diagnosis. Methods: A telephone survey of persons with idiopathic facial (Bell’s) palsy in the Greater Toronto Area (GTA, population = 4.99 million) and Nova Scotia (population = 0.93 million) from August 1 to November 15, 1997 collected information on subject demographics, neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 13 publications
3
49
1
Order By: Relevance
“…In our study, four patients (8%) showed recurrence. [14,15] Recovery rate of Bell's palsy without treatment is reported as 70%. [16] This rate reaches 90% with steroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, four patients (8%) showed recurrence. [14,15] Recovery rate of Bell's palsy without treatment is reported as 70%. [16] This rate reaches 90% with steroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The Bell's palsy characterizes by the involvement of one nerve but sometimes patients have myriad neurological symptoms like tingling sensation of the face, mild to moderate neck pain or head ache, balance problems, ipsilateral limb weakness and memory problems 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Many aetiologies have been proposed, including a viral/inflammatory mechanism 3,4 and systemic steroids and/or acyclovir been recommended as treatment. However, two population-based studies from the UK 5 and Canada 6 have estimated an incidence of 13.1-20.2/100 000. Both studies found no temporal or geographical clustering to suggest a viral aetiology.…”
Section: Idiopathicmentioning
confidence: 99%